The The Effect of Financial Performance on Stock Prices During the Pandemic - Muh. Nur Irfan Syarif; Haliah, Haliah; Kusumawati, Andi (International Journal Of Economics Social And Technology (IJEST), 2024)
This study aims to examine and analyze the effect of current ratio, debt to asset ratio, return on asset, and total asset turn over on stock price. The object of this research is the health sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022 with a total sample of 16 companies selected using purposive sampling. The data in this study are secondary data obtained from the indonesia stock exchange website and the websites of each sample company. This study uses multiple linear regression analysis. The results showed that current ratio, debt to asset ratio, and return on asset had effect on the stock price, while total asset turn over had no effect on the stock price.